The high temperature heat capacity of NpO2 - Benes̆, Ondřej; Gotcu-Freis, P.; Schwörer, Felicitas; Konings, R. J. M.; Fanghänel, Thomas (The journal of chemical thermodynamics, 2011)
The enthalpy increments of pure NpO2 have been measured using drop calorimetry in the temperature range from (376 to 1770)K. The heat capacity was derived using the obtained data constrained to 66.20J·K−1·mol−1 at 298.15K taken from published low temperature measurements. The heat capacity of NpO2 determined in this study is given by the following equation:Cp,m0/(J·K-1·mol-1)=71.608+0.015845·(T/K)-900648·(T/K)-2.